L-arginine as a novel target for clinical intervention in inflammatory bowel disease - Nüse, Björn; Mattner, Jochen (Exploration of Immunology, 2021)
Arginase-1 (Arg1) and the inducible nitric oxide synthase 2 (NOS2) compete for the common substrate L-arginine, semi-essential amino acid, and central intestinal metabolite. Both enzymes exhibit various, sometimes opposing effects on immune responses, tissue regeneration, or microbial growth and replication. In sub-mucosal tissues of patients suffering from inflammatory bowel disease (IBD), similar as in experimental colitis, the expression and activity of both enzymes, Arg1 and NOS2 are more prominent than in respective controls. Accordingly, the metabolism of L-arginine is altered in IBD patients. Thus, L-arginine represents a promising medical target for clinical intervention in these devastating diseases. Previous studies primarily focused on the host side of L-arginine metabolism. Initial reports using Arg1 inhibitors generated conflicting results in murine colitis models. Subsequently, only the generation of conditional Arg1 knockout mice allowed reliable functional analyses of Arg1 and the L-arginine metabolism in the immune system. Utilizing cell-specific conditional Arg1 knockouts, we have recently reported that Arg1, surprisingly, hampered the resolution of experimental colitis due to the restriction of the intraluminal availability of L-arginine. Reduced levels of L-arginine restrained the compositional diversity of the intestinal microbiota and subsequently the mutual metabolism between the microbiota and the host. Thus, the intraluminal microbiota represents a potential therapeutic target for L-arginine metabolism aside from host-dependent L-arginine consumption.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Arginase-1; colitis; gut microbiota; inflammatory bowel disease; intestinal metabolism; L-arginine